Pengaruh Logo dan Nilai Hedonik terhadap Loyalitas Pelanggan Dimediasi Oleh Kepuasan Pelanggan Store Buttonscraves Muara Bungo - Nuraini Nuraini; Isman Isman; Misra Yeni R (Pusat Riset dan Inovasi Nasional, 2025)
The research aims to determine the influence of Logo and Hedonic Value on Customer Loyalty, mediated by Customer Satisfaction at the Buttonscraves Store in Muara Bungo. Using a Descriptive research method and Quantitative analysis with the SmartPLS 4.0 testing tool, the number of respondents is 100 people. The results of this study directly show that the Logo (X1) significantly influences Customer Loyalty (Y), with a T-Statistic value of (2.198 > 1.96). The Logo (X1) does not influence Customer Satisfaction, with a T-Statistic value of (0.913 < 1.96). The Hedonic Value (X2) influences Customer Loyalty (Y), with a T-Statistic value of (3.750 > 1.96). Furthermore, the Hedonic Value influences Customer Satisfaction (Z), with a T-Statistic value of (10.381 > 1.96). Customer Satisfaction (Z) significantly influences Customer Loyalty (Y), with a T-Statistic value of (3.699 > 1.96). Indirectly, the Logo (X1) does not significantly influence Customer Loyalty (Y) when mediated by Customer Satisfaction (Z), with a T-Statistic of (0.895 < 1.96). Additionally, the Hedonic Value (X) significantly influences Customer Loyalty (Y) when mediated by Customer Satisfaction (Z), with a T-Statistic of (3.237 > 1.96).